1990
DOI: 10.1038/hdy.1990.7
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation in a modifier system affecting the expression of Bare mutant of Drosophila subobscura

Abstract: Genetic variation affecting the expression of Bare (Ba), a morphological mutant of Drosophila subobscura that reduces the number of bristles and is located on the 0 chromosome of this species, is reported. Our results show that 0 chromosomes extracted from a natural population (El Pedroso, Santiago de Compostela, Spain) show considerable genetic variation in modifier effect upon Ba expression. The amount of modifier variability is dependent on the chromosomal arrangement (OsT and 03÷4+7), since modifier variat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

1992
1992
2009
2009

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…The modifier effect of these wild 0 chromosomes on the phenotypic expression of the Bare mutant caused by modifier polygenes located on the 0 chromosome was also evaluated by measuring the difference in mean number of bristles between Ba! + and Va/Ba individuals (see Alvarez et al, 1990). Twelve bristles per individual (four scutellars, four dorsocentrals, two supra-alars and two postalars) of 30 BaI+ and 30…”
Section: Isogenic Linesmentioning
confidence: 99%
See 4 more Smart Citations
“…The modifier effect of these wild 0 chromosomes on the phenotypic expression of the Bare mutant caused by modifier polygenes located on the 0 chromosome was also evaluated by measuring the difference in mean number of bristles between Ba! + and Va/Ba individuals (see Alvarez et al, 1990). Twelve bristles per individual (four scutellars, four dorsocentrals, two supra-alars and two postalars) of 30 BaI+ and 30…”
Section: Isogenic Linesmentioning
confidence: 99%
“…Bare is a dominant mutant located on the 0 chromosome (map position 54.7 cM) of this species that reduces variably the number of bristles of the fly and is lethal in homozygous condition (Koske & Maynard Smith, 1954;Sperlich et a!., 1977;Loukas et a!., 1979). It has been demonstrated that 0 chromosomes derived from 404 natural populations show considerable genetic variation in modifier effect upon Ba expression (Alvarez et al, 1980(Alvarez et al, , 1990. The analysis of the genetic architecture of this modifier variability carried out using biometrical techniques for locating and mapping polygenes showed that the differences in modifier effect between a wild 0 chromosome of high modifier effect and a marker chromosome of low score can be explained by a relatively small number of polygenic modifier factors (Alvarez et al, 1981(Alvarez et al, , 1990.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations